THE ROLE OF THE FAMILY IN BUILDING IMMUNITY AGAINST INFORMATION ATTACKS (Universal International Scientific Journal, 2026)
This article discusses the influence of the family in forming youth's immunity to information attacks. Youth are the future leaders, and it is our duty to provide them with spiritual, educational and moral knowledge. But the main task lies with the parents of youth. The family is the main "SHIELD" in the formation of spiritual immunity against information attacks, and it is necessary for parents to instill in their children national values, a healthy worldview and critical thinking from an early age.
Keywords: Immunity; information attacks; family influence